The Effectiveness of Classical Music Background in Teaching Writing - Ishak; Sultan, Wahyu; Darwis, Nirwana (Inspiring: English Education Journal, 2023)
This study discusses the effectiveness of incorporating classical music in teaching writing, using a quantitative research method. The research was conducted on 39 students from two groups in the fifth semester English Educational Program of IAIN Bone, with 20 students in the experimental group and 19 students in the control group. The researcher administered pretests, treatments, and posttests, and analyzed the data using mean score and t-test formulas. The results of the study indicate that the students in the experimental group who received treatment with classical music background showed improvement in their writing achievement compared to the control group, who received treatment without the classical music background. However, the improvement was not considered significant. Therefore, it can be concluded that the use of classical music background in teaching writing did not have a significant impact on the writing achievement of fifth-semester students in the English Educational Program of IAIN Bone.